Study of the Growth Control of Nonionic Surfactant Reverse Micelles by Water and Glycerol Using Small-angle X-ray Scattering - Shrestha, Lok Kumar (Journal of Nepal Chemical Society, 2009)
This paper described a facile route to the growth control of nonionic surfactant reverse micelles in diglycerol monolaurate (C12G2)/cyclohexane systems at 25°C. Structural characterization of reverse micelles was carried out using small-angle X-ray scattering (SAXS) technique. It has found that C12G2 spontaneously formed elongated prolate type reverse micelles in cyclohexane at 25°C and the micellar size grows with CC12G2 concentration. The reverse micelles could solubilize some amount of water in the micellar core thus enhanced their potential application in the encapsulation of water-soluble drugs. Phase separation occurred with further addition of water. The micelles grow with the amount of water content in the system, as water tends to go to the micellar core swelling the micelles. However, the size decreased with increasing temperature at fixed water content. Increasing mixing fraction of glycerol in water decreased the micellar size. This would be understood as glycerol dehydrates surfactant's headgroup and increased the packing parameter. Keywords: Diglycerol monolaurat;, Cyclohexane; glycerol;, Small-angle X-ray scattering (SAXS), Reverse micelles. DOI: 10.3126/jncs.v24i0.2381 Journal of Nepal Chemical Society, Vol. 24, 2009 Page: 12-18